2000
DOI: 10.1038/sj.sc.3100968
|View full text |Cite
|
Sign up to set email alerts
|

Total spondylectomy for primary tumor of the thoracolumbar spine

Abstract: Study Design: Six patients with primary malignant tumor of the thoracolumbar spine who underwent total spondylectomy (TS) by en bloc resection were reviewed retrospectively. Objectives: To report surgical technique and preliminary results of TS and to evaluate its oncological curability. Setting: Japan. Methods: Six patients were treated by TS by en bloc resection of the vertebral tumor. TS through a posterior approach was performed in three cases (T1 osteosarcoma, L1 osteosarcoma and L1 chordoma) and in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 9 publications
3
16
0
3
Order By: Relevance
“…This study agrees with previous investigations [2,6,18,21,24,32,34,38] supporting en bloc spondylectomy for treatment of primary malignant vertebral bone tumors and solitary spinal metastasis of certain tumor entities. En bloc spondylectomy followed by dorsoventral reconstruction allowed radical resections with negative margins in all patients.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This study agrees with previous investigations [2,6,18,21,24,32,34,38] supporting en bloc spondylectomy for treatment of primary malignant vertebral bone tumors and solitary spinal metastasis of certain tumor entities. En bloc spondylectomy followed by dorsoventral reconstruction allowed radical resections with negative margins in all patients.…”
Section: Resultssupporting
confidence: 92%
“…At a mean follow-up of 32 months, we had no local recurrence. In the series by Abe et al, local recurrence was found in three cases with a mean follow-up of 38 months [2]. The low recurrence rate in our study, with no reoperation required for local relapse, may be due to both, the consequent multimodality treatment concept and the negative resection margins in all patients.…”
Section: Discussionsupporting
confidence: 47%
“…Over the decades, this technique has been considered as a risky and technically highly demanding procedure that was reserved for limited indications in some specialized centers [5,10]. In 1994, Tomita, one of the pioneers in en bloc resection of the spine, published his series of 20 spondylectomies for solitary spinal metastases [11].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years the following have been used: bicortical iliac crest grafts (Benoit et al 1990), allograft and anterior Goutallier plate (Boriani et al 1996), fibular allograft (Tomita et al 1997), tricortical iliac crest grafts (Bosma et al 2001), chest tube filled with methylmethacrylate (Marmor et al 2001) or an apatite-wollastonite glass ceramic vertebral prosthesis or a titanium mesh cage filled with iliac bone chips and augmented with Zielke or Kaneda instrumentation (Abe et al 2000(Abe et al , 2001, and mesh cages which have to be cut to obtain physiological regional lordosis. These devices are mostly not designed for L5 reconstruction and do not provide reliable primary stability.…”
Section: Discussionmentioning
confidence: 99%
“…After complete exposure of neural structures, the epidural part of the chordoma was removed. Its surface within the vertebral body was continuously covered with bone wax to prevent dissemination of tumor cells (Abe et al 2000). Finally, the posterior longitudinal ligament was horizontally transsected twice.…”
Section: Total L5 Spondylectomymentioning
confidence: 99%